2011
DOI: 10.5694/j.1326-5377.2011.tb02978.x
|View full text |Cite
|
Sign up to set email alerts
|

The domino effect: adolescent girls’ response to human papillomavirus vaccination

Abstract: Objectives: To examine the experience of fear, the fear response, and factors affecting fear in adolescents undergoing school‐based human papillomavirus (HPV) vaccination. Design, participants and setting: A purposive sampling strategy and qualitative methods, including observation and face‐to‐face interviews. Focus groups comprised adolescent girls who were involved in HPV vaccination in 2007 at schools in Sydney, New South Wales. Individual interviews were conducted with parents, teachers and vaccination nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 34 publications
5
47
0
5
Order By: Relevance
“…The USDA continuum codes can be treated as continuous or categorical (1–3=metropolitan/urban, and 4–9=non-metropolitan/rural) indicators (United States Department of Agriculture, 2013). Previous studies of the USDA continuum codes have analyzed the association between urbanicity and cancer outcomes, including screening (Litaker & Tomolo, 2007), incidence (Bernard, Cooper Robbins, McCaffery, Scott, & Skinner, 2011), stage of diagnosis (Paquette & Finlayson, 2007), and survival (Modesitt, Huang, Shelton, & Wyatt, 2006), treating the codes as either continuous or categorical.…”
Section: Methodsmentioning
confidence: 99%
“…The USDA continuum codes can be treated as continuous or categorical (1–3=metropolitan/urban, and 4–9=non-metropolitan/rural) indicators (United States Department of Agriculture, 2013). Previous studies of the USDA continuum codes have analyzed the association between urbanicity and cancer outcomes, including screening (Litaker & Tomolo, 2007), incidence (Bernard, Cooper Robbins, McCaffery, Scott, & Skinner, 2011), stage of diagnosis (Paquette & Finlayson, 2007), and survival (Modesitt, Huang, Shelton, & Wyatt, 2006), treating the codes as either continuous or categorical.…”
Section: Methodsmentioning
confidence: 99%
“…6-12 Generally, parents and adolescents have similar HPV vaccine beliefs, 11,13,14 including their risk appraisals, which predict their vaccination intentions and behaviors. However, some beliefs affect parents' and adolescents' motivations differently: The promise of preventing cancer encourages parents, 15,16 while fear of needles or pain discourages adolescents 6,9,11,17 from seeking vaccination.…”
mentioning
confidence: 99%
“…However, vaccination side effects are intrinsically more proximal to sons, and avoidance of discomfort is a powerful motivator of health behaviors, 25 including vaccination. 6,9,11,17 Finally, we examined whether the relationship between beliefs and vaccination willingness varied by the age of adolescent sons, hypothesizing that parents' beliefs would be less closely related to HPV vaccination willingness among older sons than younger sons (Hypothesis 3). We examined these hypotheses in a national sample of adolescent boys and their parents.…”
mentioning
confidence: 99%
“…This suggestion is informed by this study’s qualitative findings showing that some vaccinated girls were mainly encouraged by their friends to get vaccinated against the HPV without fully understanding the vaccination, implying that peer influence may have mitigated some of the fears associated with the vaccination. Moreover, in the study by Bernard and colleagues (Bernard et al, 2011), girls’ concern about their possible reactions in front of peers seemed to amplify fear in some cases, yet having friends available in the vaccination room to support them by holding arms or talking to them had the reverse effect. Peer influence is a known positive and negative factor in shaping adolescent attitudes about HPV vaccine (Gamble et al, 2010; Katz et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Our qualitative results showed that the introduction of the HPV vaccine had triggered several negative rumors that were likely to worry the targeted adolescents. Apparently, much of the reported worry especially concerning pain and possible physical harm from injection was anticipatory, which is a normal response to a perceived threat but an unnecessary psychological trauma if no real threat exists (Bernard et al, 2011). Qualitative findings indicated that the fear of pain and possible physical harm from injection was usually short-lived, suggesting that time was protective.…”
Section: Discussionmentioning
confidence: 99%